RANKO MATASOVIĆ, 2016: LINGVISTIČKA POVIJEST EUROPE: Zagreb: Matica hrvatska. 339 str. - Puškar, Krunoslav (Slavia Centralis, 2020)
The article presents Ranko Matasović's book Lingvistička povijest Europe (Linguistic History of Europe), published in 2016.
Keywords: review; Ranko Matasović; linguistics; Lingvistička povijest Europe; Linguistic History of Europe